Hypersonic aerodynamic force balance using temperature compensated semiconductor strain gauges - Huacheng Qiu; Yanguang Yang; Peng Sun; Genming Chao; Yousheng Wu; Yingdong Chen (Advances in Aerodynamics, 2023)
Abstract Metal foil strain gauges remain the state-of-the-art transducers for wind tunnel balances. While strain gauge technology is very mature, piezoresistive semiconductor sensors offer alternatives that are worth exploring to assess their unique benefits, such as better strain resolution and accuracy, which would enable balances to be designed with higher factors to safety and hence longer fatigue lifetimes. A new three-component balance, based on temperature compensated semiconductor strain gauges, is designed, calibrated and tested in a hypersonic low density wind tunnel. The static accuracy of the semiconductor balance is calibrated better than 0.3% FS, and the dynamic accuracy of the balance is established using a HB-2 standard model in a Mach 12 hypersonic flow. Good experimental repeatability is confirmed to be better than 2.5% FS, and the effectiveness of the balance is demonstrated by comparing the forces and moments of measured data with computational fluid dynamics simulations, as well as reference wind tunnel results under similar conditions.